2019
DOI: 10.1002/pssa.201900058
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Nickel Nitride Thin Films using NiCl2(TMPDA) and Tert‐Butylhydrazine as Precursors

Abstract: This article describes the atomic layer deposition (ALD) of nickel nitride and nickel thin films using a diamine adduct of Ni(II) chloride, NiCl 2 (TMPDA) (TMPDA ¼ N,N,N 0 ,N 0 ,-tetramethyl-1,3-propanediamine), as the metal precursor. Owing to the high reducing power of tert-butylhydrazine (TBH), the films are grown at low temperatures of 190-250 C. This is one of the few lowtemperature ALD processes that can be used to grow Ni 3 N and Ni metal on both insulating and conductive substrates. The films are chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Here, it is worth mentioning that those Ni 4 N films were either deposited at a high Tnormals (about 625 K) or some impurity of Ni phase was present. [ 30–32 ] In addition, the crystal structure of Ni 4 N seems to be unclear hitherto. Two different possible structures for Ni 4 N have been observed namely Ni 4 N‐I and Ni 4 N‐II.…”
Section: Figurementioning
confidence: 99%
“…Here, it is worth mentioning that those Ni 4 N films were either deposited at a high Tnormals (about 625 K) or some impurity of Ni phase was present. [ 30–32 ] In addition, the crystal structure of Ni 4 N seems to be unclear hitherto. Two different possible structures for Ni 4 N have been observed namely Ni 4 N‐I and Ni 4 N‐II.…”
Section: Figurementioning
confidence: 99%
“…This may indicate the decomposition of TBGH, as we have previously shown that NiCl 2 (tmpda) starts to decompose only at temperatures above 250 °C. 21 Another possibility is that the film is etched by the by-product HCl and the free tmpda ligands or that these start to block the surface sites from the precursor molecules. It is also possible that the precursor doses were insufficient for the highest growth rate so that the precursors were consumed before reaching the outlet edge of the substrate.…”
Section: ■ Resultsmentioning
confidence: 77%
“…The precursor decomposes at temperatures above 250 °C. 21 NiCl 2 (tmpda) can be prepared from inexpensive starting materials with a high yield and is thus a good ALD precursor also from an industrial point of view. The compound is synthesized simply by mixing NiCl 2 solution with a threefold excess of the amine and refluxing for 3 h. A more detailed description of the synthesis can be found in the literature.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a chemistry-based technique, ALD requires the use of appropriate chemicals. For the deposition of nickel, many metal organic compounds have been tested, including nickel tetracarbonyl (Ni­(CO) 4 ), nickel cyclopentadienyls such as bis­(cyclopentadienyl)nickel (NiCp 2 ), bis­(methylcyclopentadienyl)­nickel (Ni­(MeCp) 2 ]), bis­(ethylcyclopentadienyl)­nickel (Ni­(EtCp) 2 ), , and (η 3 -cyclohexenyl)­(η 5 -cyclopentadienyl)nickel (Ni­(Chex)­(Cp)]), nickel diamines such as NiCl 2 ( N , N , N ′, N ′,-tetramethyl-1,3-propanediamine) (NiCl 2 (TMPDA)), , diazadienyls such as bis­(1,4-diisopropyl-1,3-diazabutadienyl)­nickel (Ni­( i Pr-DAD) 2 ) and bis­(1,4-di- tert -butyl-1,3-diazabutadienyl)nickel (Ni­( t But-DAD) 2 ), nickel acetamidinates such as bis­( N , N ′-diisopropylacetamidinato)nickel (Ni­( i Pr-amd) 2 ) and bis­( N , N ′-di- tert -butylacetamidinato)­nickel (Ni­( t But-amd) 2 ), β-diketonates such as bis­(acetylacetonate)nickel (Ni­(acac) 2 ) and bis­(2,2,6,6-tetramethyl-3,5-heptanedionate)nickel (Ni­(TMHD) 2 , or Ni­(thd) 2 ), mixed nickel diamine-diketonates such as ( N , N , N ′, N ′-tetramethylethylenediamine)­(bis­(2,4-pentanedionato)­nickel (Ni­(acac) 2 (tmeda)), , and nickel amino-alkoxides such as bis­(1-dimethylamino-2-methyl-2-butoxide)nickel (Ni­(dmamb) 2 ). …”
Section: Introductionmentioning
confidence: 99%